2019
DOI: 10.1021/acsphotonics.8b01413
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Feedback Lasers and Light-Emitting Diodes Using 1-Naphthylmethylamnonium Low-Dimensional Perovskite

Abstract: This work investigates the feasibility of using lowdimensional perovskites for electrically driven lasers given the current status of perovskite light-emitting diodes and optically pumped lasers. In our progress toward electrically driven lasers, we performed a variety of measurements on bulk and lowdimensional perovskite films to give a baseline for expectations. This included the measurement of amplified spontaneous emission, lasing, and near-infrared light-emitting diodes operated at low and high current de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 26 publications
1
59
0
Order By: Relevance
“…Recently, researchers reported both amplified spontaneous emission and lasing at room temperature in quasi‐2D thin films [ 69,76–81 ] making them promising gain materials. Li et al.…”
Section: Perovskite Gain Materialsmentioning
confidence: 99%
“…Recently, researchers reported both amplified spontaneous emission and lasing at room temperature in quasi‐2D thin films [ 69,76–81 ] making them promising gain materials. Li et al.…”
Section: Perovskite Gain Materialsmentioning
confidence: 99%
“…[ 22 ] Since then, there have been several reports on ASE and lasing in quasi‐2D perovskite materials. [ 24–26 ] It is demonstrated that a graded domain distribution is favorable for efficient energy funneling, [ 27,28 ] in which the amount of low‐bandgap acceptors is larger than the high‐bandgap donors. Thus, it is able to achieve high quantum yield as well as enhanced LED performance.…”
Section: Figurementioning
confidence: 99%
“…Recently, the amplified spontaneous emission (ASE) and lasing behaviors of 2D RPPs have been demonstrated . However, the lasing is mostly obtained from solution‐processed spin‐coated thin films, in which multiple RPP components inevitably form with different bandgaps that drive cascade carrier transfer and may reshape the build‐up of population inversion .…”
Section: Auger Decay Lifetime (τAuger) At High Excitation Fluence (P mentioning
confidence: 99%